Prevalence and Predictors of Atopy in HIV/AIDS Patients - Tesiman, Jimmy; Sundaru, Heru; Karjadi, Teguh H.; Setiati, Siti (UI Scholars Hub, 2016)
Introduction. HIV infection attacks the center of immune control system resulting opportunistic infection, malignancy and death. Immune system dysregulation plays the central role in the progression of the disease. Some studies reported that HIV-infected patient prone to have allergic disease such as sinusitis, asthma and atopic dermatitis. Elevated serum immunoglobulin E (IgE) and increased prevalence of atopy had also been reported in HIV-infected patient. Methods. A cross sectional study was performed in 92 HIV-infected persons and 90 non-HIV persons. Atopy diagnosis was based on immediate hypersensitivity to six common aeroallergen using skin prick test. CD4 cell count, total serum immunoglobulin level and medical history were taken. Results. Among total of 92 HIV/AIDS patients and 90 non-HIV persons, there were 65 males (70.7%) and 27 female (29.3%) in HIV group and 40 males (44.4%) and 50 females (55.6%) in non-HIV group. Age of all subjects range from 20 to 55 years old, mean age of HIV-infected patients was 29.3 (SD 5.7) years while mean age of controls was 27.9 (4.5) years old. Based on HIV route transmission, there were 56.5% subjects infected from intravenous drug user, 38% from heterosexual intercourse and 5.5% subjects had both risk. CD4+ lymphocyte counts of the subject range from 2-674 cells, median 160 cells/uL. Serum total IgE levels range from 3-20.000 IU/mL with median 283.5 IU/mL. Atopy was higher in subjects with HIV than non-HIV (p= 0,001). The most common aeroallergen is Dermatophagoides farinae (50%) and Dermatophagoides pteronyssinus (30%). There was a negative correlation between CD4+ lymphocyte count and total IgE level (r=-0,544, p<0,001), but there is no relation between gender, HIV route of transmission, allergic history in family and CD4+ lymphocyte count with atopy. Conclusions. Prevalence of atopy based on skin prick test among HIV/AIDS patients was higher than non-HIV group. There was a negative correlation between CD4+ lymphocyte count and total IgE level.